Lei e sexualidade: um estudo psicanalítico sobre os crimes de estupro - Inada, Jaqueline Feltrin (2017)
This study aimed to analyze, based on Freud's psychoanalysis, the laws regarding rape crimes in the Criminal Code, using as an illustration two cases, already filed, in which the defendants were convicted of committing sexual offenses. To this end, the following question was sought: what is the conception of human nature that underlies criminal law? Aiming to insert the law in life, the stories of Joel and Elias were initially presented and then their respective victims, Ana and Luna. In order to establish a bridge between these stories, the law and the theories left by Freud, psychoanalysis was used as theory and method. The conceptions of human nature, law, perversion and psychopathy were thus studied and, in this process, it was possible to find resonances between the cases and Freudian concepts. Furthermore: through an interpretive work, an understanding about the stories was constructed. It was thus understood that, although the laws on rape crimes retain a conception of human nature close to that formulated by Freud, in guiding by the assumption that human beings are aggressive and sexual, they miss important discoveries revealed By psychoanalysis, which relate to the cleavage of the Self, to refusal, to the stability of perversion, and to the peculiarities of the Super-Self. Because of these findings, it was concluded that psychoanalysis has much to contribute to the development of penal practices that are more beneficial to society